المهارات الحياتية كما تعكسها برامج الأطفال بالقنوات الفضائية العربية لطفل ما قبل المدرسة: دراسة تحليلية - الجيار، سلوى علي إبراهيم (جامعة الأزهر - كلية الإعلام بالقاهرة, 2018)
هدفت الدراسة رصد وتحليل المهارات الحياتية المقدمة ببرامج الأطفال بالقنوات الفضائية العربية لطفل ما قبل المدرسة، واعتمدت الباحثة على منهج المسح بالعينة بشقه التحليلي، وتمثل ذلك في مسح مضمون عينة عمدية من برامج الأطفال التي تقدمها القنوات الفضائية العربية، وذلك بهدف التعرف على المهارات الحياتية التي تركز عليها هذه البرامج خلال فترة التحليل، وتمثلت عينة الدراسة في برامج (تيلا تولا – افتح يا سمسم ج 3- بنات وولاد)، وذلك خلال دورة برامجية مدتها ثلاثة أشهر بدأت من 1/ 4/ 2018م، وحتى 30/ 6/ 2018م، وتوصلت نتائج الدراسة إلى: - تنوع المهارات الحياتية التي تناولتها برامج الأطفال عينة الدراسة وقد اشتمل كل برنامج على معالجة اكثر من مهارة من المهارات حيث وضح ذلك واشتملت على (1990) مهارة تم تناولها خلال فترة الدراسة، حيث جاء برنامج أفتح يا سمسم ج3 في مقدمة برامج الأطفال التي تناولت المهارات الحياتية لطفل ما قبل المدرسة بواقع (962) مهارة وبنسبة بلغت (48.3%)، يليها في الترتيب الثاني برنامج تيلا تولا بواقع (805) مهارة بنسبة بلغت (40.5%)، ثم جاء برنامج بنات وولاد في الترتيب الثالث لبرامج الأطفال التي تناولت المهارات الحياتية لطفل ما قبل المدرسة بواقع (223) مهارة بنسبة (11.2%). - كما احتلت مهارات القيادة مقدمة المهارات الحياتية التي وردت في برامج الأطفال عينة الدراسة بنسبة بلغت (22.5%)، بينما جاء في الترتيب الثاني مهارات التواصل الاجتماعي بواقع (394) مهارة بنسبة بلغت (19.8%)، يليها في الترتيب الثالث للمهارات الحياتية التي وردت في برامج الأطفال عينة الدراسة "مهارات ذهنية" بنسبة بلغت (14.5%)، ثم جاء مهارات التعامل مع البيئة في الترتيب الرابع للمهارات الحياتية التي وردت في برامج الأطفال عينة الدراسة بنسبة بلغت (14.0%).
The study aims at monitoring and analyzing the life skills provided by the children's programs in the Arabic satellite channels for preschool child. The researcher depended on the sample survey method in its analytical part. This represented in analyzing the content of an intentional sample of children programs which the Arab satellite channels displayed in order to know the life skills which these programs focused during the analysis period. The study sample represented in (Tela Tula - Open sesame Part 3- Girls and Boys) programs, during a three-month program cycle that began from 4/1/2018 to 6/30/2018. The results of the study are the following:- - The life skills were various which the children programs dealt with. Each program included the treatment of more than one skill. The programs included (1990) skills that were dealt during the study period. Open sesame program Part 3 came at the top of the children programs which dealt with the life skills for pre -school child with (962) skills and with percentage (48.3%), followed in the second rank Tela Tula program with (805) skills and with percentage (40.5%), then came “girls and boys” program in the third rank for children's programs that dealt with the life skills for the Pre-school child with (223) skills and with percentage (11.2%). - The leadership skills were at the top of the life skills that were mentioned in the programs of the study sample and with percentage (22.5%), while social communication skills came in the second rank with (394) skills and with percentage (19.8%), followed in the third rank of the life skills displayed in the children programs for the study sample "mental skills" with percentage (14.5%) and then came the skills of dealing with the environment in the fourth rank of the life skills, which was mentioned in the children programs of the study sample with percentage (14.0%).
Keywords: الإعلام العربي -- وسائل الإعلام -- القنوات الفضائية -- برامج الأطفال -- المهارات الحياتية